Twenty‐Year Outcome After Right Ventricular Outflow Tract Repair Using Heterotopic Pulmonary Conduits in Infants and Children. Issue 1 (1st December 2015) - Hoxha, Stiljan; Torre, Salvatore; Rungatscher, Alessio; Sandrini, Camilla; Rossetti, Lucia; Barozzi, Luca; Faggian, Giuseppe; Luciani, Giovanni Battista
Abstract: Durability of pulmonary conduits (PCs) used for reconstruction of the right ventricular outflow tract (RVOT) may be affected by a variety of factors. Among these, the technique used for PC implantation, whether in orthotopic or heterotopic position, strictly dependent upon the underlying anatomy, has been suggested to influence long‐term outcome after RVOT repair. To determine the outcome of heterotopic implantation in infants and children treated at our institution, late results of heterotopic PC in non‐Ross patients were analyzed and compared with data of orthotopic PC in age‐matched pediatric Ross patients operated during the same time period. Between November 1991 and January 2015, 58 infants and children, 32 male and 26 female, with a median age of 9.4 years (range 1 day–18 years) underwent implantation of heterotopic PC (31 homografts [HG] and 27 xenografts [XG]) for reconstruction of RVOT. Median age in the XG group was significantly lower than in the HG group (0.9 vs. 13.4 years, P = 0.01), while male/female ratio was similar. Fifty (86%) patients had undergone one or more prior cardiac operations, while 32 (55%) required associated procedures during PC implantation. Comparison with data in 305 children and with a median age of 9.4 years, receiving orthotopic PC between 1990 and 2012 (Italian Pediatric Ross Registry), was undertaken. Descriptive, univariate, and Kaplan–Meier analysis defined outcome. There were three (5.2%) early and five (9.0%) late deaths, during a median follow‐up of 7.6 years (range 2 months–23 years). Patients having XG had trend toward higher hospital mortality (2/27 vs. 1/31, P = 0.2), but similar late mortality (2/24 vs. 3/30, P = 0.3). Overall survival was 88 and 62%, while freedom from PC replacement was 49 and 21%, at 10 and 20 years, respectively. The latter proved significantly worse than freedom from orthotopic PC replacement, which was 94 ± 2 and 70 ± 9% at 10 and 20 years ( P = 0.02). When stratified for type of heterotopic PC, late survival proved comparable (81 and 81% for XG vs. 92 and 60% for HG, at 10 and 20 years, respectively, P = 0.7). However, freedom from PC replacement was significantly higher in patients with heterotopic HG (21 and 5% for XG vs. 63 and 48% for HG, at 10 and 20 years, respectively, P = 0.001). RVOT repair using either XG or HG in heterotopic position is a safe procedure associated with low hospital mortality and satisfactory late survival. Freedom from reoperation is significantly lower than that observed in age‐matched children having orthotopic HG. Freedom from reoperation in heterotopic XG is poorer than in HG, although different baseline demography may have influenced this finding.